WHAT DRIVES CONSUMERS IN USING DIGITAL APPS TO VISIT HALAL TOURISM IN EAST JAVA? OPTIMIZATION STRATEGY FROM UTAUT2 PERSPECTIVE - Yan Putra Timur; Mohamed Battour; Ririn Tri Ratnasari; Siti Zulaikha (Universitas Airlangga, 2023)
This study aims to identify the factors influencing consumer behavioral intentions in using digital applications to visit halal tourist attractions using the UTAUT2 model approach. PLS-SEM was employed as the quantitative research method's evaluation model. 300 respondents, ranging in age from 17 to 65, were utilized as the sample. Using a Likert scale from 1 to 5, a scale generated from earlier research is used to measure each variable. The study's findings revealed that five UTAUT2 indicators”performance expectancy, effort expectancy, social influence, pricing value, and habit”positively influenced consumers' inclinations to use digital applications to visit halal tourism locations. Based on the IPMA test, the performance expectancy variable is the variable that has the highest level of importance. The results of this study can be used by halal tourism business actors and the government as a digital application strategy development to support the growth of halal tourism in East Java.